2015
DOI: 10.1039/c5cc02459e
|View full text |Cite
|
Sign up to set email alerts
|

A short pyrene-fused pyrazaacene with red to near-infrared photoluminescence

Abstract: A pyrene-fused pyrazaacene with only four linearly-fused aromatic rings is reported, which remarkably shows emission at red to NIR wavelengths (λ(em) = 687 nm). This exceeds the emission wavelengths observed for azaacenes with the same number of linearly-fused rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…The CT character of these derivatives is even more evident when comparing them to their analogues without the donor moieties at the 2,7‐positions. Mateo‐Alonso and co‐workers reported that λ max (abs)=455 nm for VII , the analogue of our derivative 7 , which demonstrates that the resulting CT character introduced via the additional donors causes a bathochromic shift of 3500 cm −1 of the S 1 ←S 0 absorption in our systems. Compound VIII , the analogue of our derivative 8, has λ max (abs)=435 nm according to Sahoo et al.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The CT character of these derivatives is even more evident when comparing them to their analogues without the donor moieties at the 2,7‐positions. Mateo‐Alonso and co‐workers reported that λ max (abs)=455 nm for VII , the analogue of our derivative 7 , which demonstrates that the resulting CT character introduced via the additional donors causes a bathochromic shift of 3500 cm −1 of the S 1 ←S 0 absorption in our systems. Compound VIII , the analogue of our derivative 8, has λ max (abs)=435 nm according to Sahoo et al.…”
Section: Resultssupporting
confidence: 54%
“…Hence, the electronic coupling V between the localized mixed valence states yields V = 1279 cm À1 for 7 + and I [15] 475 (hexane) 511 (hexane) -À0.18 (CH 2 Cl 2 ) + 0.26 (CH 2 Cl 2 ) 481 (THF) 525 (THF) II [15] 450 (hexane) 464 (hexane) À2.51 (THF) + 0.29 (THF) 462 (THF) 497 (THF) III [32] ---+ 0.14 (CH 2 Cl 2 ) + 0.38 (CH 2 Cl 2 ) IV [28] 453 (toluene) 482 (toluene) ---V [41] 630 (CHCl 3 ) -À0.67 (CHCl 3 ) + 0.39 (CHCl 3 ) -VI [40] 575 (CHCl 3 ) -À1.04 (CHCl 3 ) + 0.33 (CHCl 3 ) -VII [45] 455 (CH 2 Cl 2 ) 538 (CH 2 Cl 2 ) À1.43 (THF) --VIII [46] 435 (CH 2 Cl 2 ) 471 (CH 2 Cl 2 ) --- 2 , which shows that these compounds are class-II compounds, but lie close to the borderline between localized class-II and delocalized class-III compounds, as V is quite large. This result is also in line with the observed broad and asymmetric band shape.…”
Section: Spectroelectrochemistrymentioning
confidence: 99%
“…Half-wave potentials (E red , E ox ) were recorded from square wave voltammetry. Position of the first reduction potential (E red 1 ) reflected more less electron donating and withdrawing character of the substituents in positions 6 and 7 expressed by Hammett substituent constant (s p ) making hetaryl substituted derivatives strongly electrondeficient approximately on the same level as remarkable electron-deficient pyrene-fused azatetraacenes reported recently [6]. A substantial shift of the E red 1 toward positive values observed in this work are also in good agreement with the results observed by Song et al in the series of aza-analogues of naphthalene-dicarbonitriles who observed substantial cathodic shift with increasing number of nitrogens in the heterocycle with substituted pyrazino[2,3-b]pyrazine-2,3-dicarbonitrile being the most electron-deficient [10].…”
Section: Electrochemistrymentioning
confidence: 80%
“…In particular, pyrazino [2,3-b]pyrazine fragment can be found in number of interesting compounds with strong electron-accepting character [1][2][3] that were investigated for charge transfer properties in liquid crystals [4], as n-type transistors in field-effect transistors [5] or as redemitting fluorophores where the red-shift was caused by highly polarized structure [6]. However, number of efforts of introduction of pyrazino [2,3-b]pyrazine fragment into porphyrazines forming thus tetra(pyrazino [2,3-b] pyrazino)porphyrazines (TPyzPyzPzs), a macrocycle with potentially strongly electron-deficient character, failed.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Mateo-Alonso's group reported a new pyrenefused azaacene (48) with four linearly fused rings (Scheme 16); interestingly, its maximum emission wavelength reached from 687 nm to the NIR region. [39] Moreover, a pyrene-fused phenazinothiadiazole (49) was also synthesized by them, [40] which showed electron mobilities (m e…”
Section: Single Terminal-pyrene Unitsmentioning
confidence: 99%